Elemen Keseimbangan Dalam Tumbuhan Menurut Al-Quran: Satu Tinjauan Awal - Siti Nurwanis Mohamed; Monika@Munirah Abd Razzak; Najihah Mohd Hashim (USIM Press, 2024)
Vol. 5 No. 1 (2020): Jurnal Sains Insani